Tanzania : Sixth Review Under the Poverty Reduction and Growth Facility and Requests for Waiver of a Performance Criterion and for a New Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Press Release on the Executive Board Discussion for Tanzania; and Statement by the Executive Director for Tanzania. (IMF Staff Country Reports; Country Report, 2003)
Tanzania showed strong economic growth owing to its sound macroeconomic policies and structural reforms, under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors commended this step, and emphasized for higher revenue mobilization through reforms of tax administration and tax policies. They encouraged the authorities to fight corruption, enhance governance, and stressed the need to maintain fiscal consolidation and accelerate structural reforms. They agreed that Tanzania has successfully completed the sixth review under the PRGF Arrangement, and granted waiver.